Biological Activity of Lenalidomide and Its Underlying Therapeutic Effects in Multiple Myeloma - Roberta Martiniani; Valentina Di Loreto; Chiara Di Sano; Alessandra Lombardo; Anna Marina Liberati (Advances in Hematology)
Lenalidomide is a synthetic compound derived by modifying the chemical structure of thalidomide. It belongs to the second generation of immunomodulatory drugs (IMiDs) and possesses pleiotropic properties. Even if lenalidomide has been shown to be active in the treatment of several hematologic malignancies, this review article is mostly focalized on its mode of action in multiple myeloma. The present paper is about the direct and indirect antitumor effects of lenalidomide on malignant plasmacells, bone marrow microenvironment, bone resorption and host’s immune response. The molecular mechanisms and targets of lenalidomide remain largely unknown, but recent evidence shows cereblon (CRBN) as a possible mediator of its therapeutical effects.